A CRITICAL DISCOURSE ANALYSIS OF THE AUTHOR’S RHETORICAL STRATEGIES TO REVEAL THE STRUGGLE OF IDEOLOGY IN RICHARD MANN’S PLOTS AND SCHEMESTHAT BROUGHT DOWN SOEHARTO - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2008)
The study explored the rhetorical strategies employed by Richard Mann in writing a political textbook entitled ‘Plots and Schemes that Brought down Soeharto’ in order to reveal the struggle of ideology of both the hegemonic reforms (the reformists’ side) and the hegemonic maintenance (Soeharto’s regime). Employing Appraisal Theory (White 1998; Martin & Rose 2003), Genre Theory (Chandler, 1997), and Text Framing (MacLachan, G. and Reid, I. 1994), the textbook was analysed in terms of micro-, super-and macro-structures. On the level of microstructure, the readers were positioned as pro-reformists and against Soeharto’s regime. The superstructure analysis indicated that the textbook was written following the tradition of plots: orientation ^ mounting incidents ^ climax ^ denouement. The climax part was when Soeharto stated his resignation from presidency, followed by the denouement (the Habibie’s regime). Macrostructurally, the textbook was written in academic perspective of journalistic style employing the rhetorical strategies (Strayer 2004), such as downplayers, weaslers, dysphemism, euphemism, innuendo, loaded questions and horse-laughs. Since the study was pedagogically motivated, several issues, such as the development of literacy, the development of linguistic analyses (from non-critical to critical) were discussed at philosophical level to justify that the current study was critical discourse analysis. Key Words: Critical Discourse Analysis, Rhetorical Strategies, Hegemonic Reform, Hegemonic Maintenance, APPRAISAL, Microstructure, GENRE (superstructure), Macrostructure.